2020
DOI: 10.1080/20008198.2020.1760481
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of ICD-11 and DSM-5 criteria for PTSD among a representative sample of Chinese earthquake survivors

Abstract: Background: Striking differences regarding the diagnosis of PTSD exist between the ICD-11 and DSM-5. This study compared the prevalence and comorbidity of PTSD between the ICD-11 and DSM-5. Methods: An epidemiological sample of 1160 Chinese adult earthquake survivors collected nine and a half years following the Wenchuan earthquake, in Sichuan province. The PTSD Checklist for DSM-5 (PCL-5), the Patient Health Questionnaire (PHQ-9), and the Generalized Anxiety Disorder-7 (GAD-7) were used to measure PTSD, depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…For example, expressing psychological distress is considered a dilemma in Chinese culture. People who experience psychological problems tend to attribute these problems to physical or external origins [ 44 , 59 ]. This might be the reason that psychological problems were often expressed in the form of physical illness in Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, expressing psychological distress is considered a dilemma in Chinese culture. People who experience psychological problems tend to attribute these problems to physical or external origins [ 44 , 59 ]. This might be the reason that psychological problems were often expressed in the form of physical illness in Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…симптомов, составляющих основу для выделения в отдельную таксономическую единицу так называемого «осложненного ПТСР». Неудивительно в связи с этим, что диагнозы ПТСР, устанавливавшиеся в одной и той же выборке, но по разным диагностическим критериям (МКБ-11 и DSM-5), совпадают менее чем в 50% случаев [8,9].…”
Section: динамика представлений о диагностических критериях птсрunclassified
“…In a sample of trauma survivors from China ( n = 1060), Cao et al. 33 found that the disagreement rate of diagnosis of probable PTSD between ICD-11 and DSM-5 was relatively high (ICD-11 vs. DSM-5: 43.6% (102/234 participants), but there was no significant difference on PTSD's comorbidity of major depressive disorder or generalized anxiety disorder. Six-factor models (the Anhedonia model, 34 the Externalizing Behavior model 35 ) have also been proposed.…”
Section: Present Of Ptsdmentioning
confidence: 99%